CYP1A1 and CYP2D6 Gene Polymorphisms in Israeli Jewish Women With Cervical Cancer. Issue 8 (1st November 2009) - Gutman, Guy; Morad, Tova; Peleg, Ben; Peretz, Chavah; Bar-Am, Amiram; Safra, Tamar; Grisaru, Dan
Abstract : Hypothesis: To assess the frequency distribution of the CYP1A1 and CYP2D6 gene polymorphisms in Israeli Jewish women with cervical cancer. Methods: Forty-three Israeli Jewish women with cervical cancer and 123 healthy Israeli Jewish women were assessed. CYP1A1 (2 alleles) and CYP2D6 polymorphism was analyzed using an allele-specific, polymerase chain reaction-based method. Results: The allele frequency and genotype distribution for the CYP1A1 (2 alleles) and CYP2D6 polymorphism did not reach a level of significance. Smoking was the only independent risk factor for cervical cancer ( P = 0.0003). Conclusion: CYP1A1 and CYP2D6 mutations are not related to an increased risk for cervical cancer in the Jewish Israeli population.